Epithelial-Mesenchymal Transition during Metastasis of HPV-Negative Pharyngeal Squamous Cell Carcinoma. (6th March 2018) - Ihler, Friedrich; Gratz, Ronja; Wolff, Hendrik A.; Weiss, Bernhard G.; Bertlich, Mattis; Kitz, Julia; Salinas, Gabriela; Rave-Fränk, Margret; Canis, Martin
Abstract : In epithelial tumors, a shift towards a mesenchymal phenotype has been associated with increased invasiveness and metastasis. It is assumed that this phenomenon plays a major role in disease progression and ultimately prognosis. This study investigated epithelial-mesenchymal transition (EMT) in human papillomavirus- (HPV-) negative pharyngeal squamous cell carcinoma. Tissue was obtained from one hypopharyngeal primary tumor and a regional lymph node metastasis during surgery with curative intention. A cell culture was established from the primary tumor and mesenchymal growth conditions were emulated. Gene expression profiling was performed (Human 8 × 60 K design array, Agilent Technologies) and EMT was assessed by a gene set (MSigDB: M5930, Hallmark_epithelial_mesenchymal_transition), applying gene set expression analysis (GSEA). Immunohistochemical staining and flow cytometry of CD44 and E-cadherin were compared in primary tumor, metastasis, and cell cultures. Primary tumor and metastasis were highly positive for CD44. A loss of E-cadherin occurred in the metastasis. Flow cytometry showed the appearance of a population without E-cadherin in spheroid colonies. In GSEA, the EMT phenotype was enriched in the primary tumor compared to metastasis and cell cultures (FDR < 25%, p < 5%). EMT showed variable expression during metastasis. It may thereby be a dynamic state in HPV-negative pharyngeal squamous cell carcinoma that is active only during the process of metastasis itself. Thereby, the primary tumor as well as the metastasis may exhibit fewer EMT properties.